Real-world sensor dataset for city inbound-outbound critical intersection analysis - Ei Ei Mon; Hideya Ochiai; Patrachart Komolkiti; Chaodit Aswakul (Scientific Data, 2022)
Measurement(s) traffic data Technology Type(s) cctv camera • thermal camera • loop coil • taxi